The Impact of Game Design Elements on EFL Vocabulary Acquisition and Iranian Learners’ Attitudes: A Study of Cinematic, Narrative, and Quest-Oriented Games - Pedram, Parvaneh; Fahandezh Saadi, Farhad; Afraz, Shahram (Assessment and Practice in Educational Sciences, 2025)
This study investigates the impact of games on language learning and learner attitudes in an EFL context, supported by teachers' attitudes and learners' feedback. This study initially conducted qualitative interviews among language learners to identify the prominent factors in their use of learning games. Based on these results, a Likert scale survey was developed to assess learner attitudes on four aspects: cinematic presentation, level of narrative, structure of quest, and learning experience. The survey was administered to 60 students who were educated through game-based instruction. Descriptive statistics revealed a quest-oriented structure, with the highest mean score (M = 3.829) due to its significant contribution to maintaining learner motivation, and cinematic quality with the lowest mean score (M = 2.358). Cronbach's alpha reliability testing also established good internal consistency for all variables (α = 0.714 to 0.780). In addition, a comparison of pre- and post-test scores revealed a remarkable improvement in language performance, as reflected in a mean difference of 13.800. To determine if gender-dependent differences exist in students' attitudes toward game-based learning, a Mann-Whitney U test was utilized; the results revealed no significant differences on all measured dimensions (p > 0.05). The findings suggest that narrative and quest-oriented games can significantly enhance learner interest and language recall. However, cinematic aspects may have a minimal impact on learning performance. The work contributes to the growing research on language learning through games by emphasizing the importance of goal-driven, interactive game design over surface decoration.